Anna Kelton Wiley papers - Wiley, Anna Kelton, 1877-1964.; Campbell, William S. (William Shaw), 1818-1904.; Kelton, J. C. (John Cunningham), 1828-1893.; Wiley, Harvey Washington, 1844-1930.
Correspondence, speeches, reports, articles, notes, appointment books, family papers, financial records, clippings, printed matter, scrapbooks, photographs, and other papers relating chiefly to Wiley's activities on behalf of women's rights as well as child welfare, consumer protection, and Indian rights. Documents her membership and work in associations and clubs including the American Pure Food League; Columbian Women, George Washington University; District of Columbia Federation of Women's Clubs; General Federation of Women's Clubs; Housekeepers' Alliance; Kalorama Citizens' Association, Washington, D.C.; National Consumers' League; National Woman's Party; Twentieth Century Club, Washington, D.C.; and Women's City Club, Washington, D.C. Includes papers of Wiley's husband, Harvey Washington Wiley; her father, J.C. Kelton; her grandfather, William S. Campbell; and other family members.
Consumers' rights reformer, feminist, and clubwoman of Washington, D.C.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Wiley family; American Pure Food League; Columbian Women, George Washington University, Washington (D.C.); District of Columbia Federation of Women's Clubs; General Federation of Women's Clubs; Housekeepers' Alliance; Kalorama Citizens Association (Washington, D.C.); National Consumers' League; National Woman's Party; Twentieth Century Club (Washington, D.C.); Women's City Club (Washington, D.C.); Child welfare; Consumers; Consumers' leagues; Indians of North America -- Legal status, laws, etc; Women; Women -- United States -- Societies and clubs; Women -- Washington (D.C.) -- Societies and clubs; Women's rights; Washington (D.C.) -- Social life and customs; Clubwomen; Feminists; Reformers